Potato purple top and the psyllid in Ecuador 2017-2021 - Agencia de Regulación y Control Fito y Zoosanitario; International Potato Center (International Potato Center, 2024)
Purple top and the psyllid are serious problems for potato production in Ecuador. These problems can also affect other crops that belong to the Solanaceae family such as golden berry, chilli peppers, and tomato. In the case of Ecuador, there are different actors making efforts to contain purple top and the potato psyllid in the country. Agronomic practices to manage these problem include crop rotation with other local alternatives such as maize or forage crops. However, other alternatives to manage purple top and the psyllid are under investigation and not ready yet. Currently, both problems are disseminating south towards Peru.